Pengaruh Kendali Turbulensi Aliran terhadap Bidang Aliran Di Sekitar Struktur Persegi - Samhuddin; La Ode Ahmad Barata; Nurjannah Yusman (Piston: Jurnal Teknologi, 2023)
The characteristics of the flow passing over the structure affect the stability, aerodynamic design and response of the structure to the flow patterns passing over it. This study numerically examines the effects of using a splitter plate on the velocity pattern, pressure, aerodynamic forces and flow deformation at a Reynolds number of 104. This study used a 2D double-type flow splitter on the downstream side with a k-ε turbulent model using ANSYS FLUENT 18.2 software. Numerical simulation results show that the use of splitter plate has changed the flow pattern passing through the square cylinder which is indicated by the reduction of negative flow zone, pressure recovery, and decrease of drag force. The flow deformation pattern is different from the cylinder without a splitter plate. Numerical data are also shown in the form of flow contours to verify the graphical data shown in the present study. This study also shows that the use of a splitter plate also shows different grid sensitivity from a regular square cylinder, so the grid sensitivity validation-verification test of a cylinder with a splitter plate is not recommended for similar cases.